The 1979 Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) - Vinković, Mario (The Universal Protection of Human Rights, 2026)
Abstract: CEDAW is the most important universal source of protection of women’s rights, which has influenced the emergence of a number of regional legal sources in the last four and a half decades. This chapter is dedicated to the importance and significance of CEDAW both in the global context of protection of women’s rights, and in relation to relevant regional legal sources, primarily of the Council of Europe. The nomotechnical architecture of CEDAW is a kind of novum that has shifted processes and normative momentum from a symmetrical approach to the protection of women’s rights to an asymmetrical and gender-focused track, and has post festum influenced the nomotechnical architecture and approaches of a number of relevant international, regional and national legal sources. The chapter also focuses on relevant decisions of the CEDAW Committee from a regional perspective.Keywords: CEDAW, women, discrimination, gender equality, regional legal sources, Istanbul Convention